Challenges in curbing illegal orthodontics in Malaysia: A qualitative study on dental law enforcement - Cheong, Joo Ming; Bahar, Aufa Dahlia; Kamarudin, Yasmin; Mohd Nor, Nor Azlida; Zainal Abidin, Haznita (2022)
Background: Braces are popular among teens in Southeast Asia because they are commonly associated with social status. This has led to a rise in the trend of fake braces, which are sold on the illegal market. Fake braces have raised public health concerns in Malaysia and despite ongoing efforts to increase public awareness of the issue, this unethical business remains unalarmed especially on social media platforms.